Referência ao discurso do outro: uma análise de problemas de relações de sentido entre discurso citado direto e indireto citante no gênero monográfico - Bessa, José Cezinaldo Rocha (2007)
In this study we investigate the reference to other s discourse done it through the resource of direct cited discourse at background section in monographic texts produced by university students at the last phase of final work in their graduate Letras course. This work is guided in cited/related discourse studies in Bakhtin (2004), Authier-Revuz (1990, 1998, 2004), Maingueneau (1996, 2002), Charaudeau and Maingueneau (2004); in genre approaches developed by Bakhtin (2000); Maingueneau (1996, 2002); socio-discursive interaction (BRONCKART, 1999, 2003; SCHNEUWLY, 2004; DOLZ e SCHNEUWLY, 2004) and Bazerman (2005); and also in presuppositions of Textual Linguistics presented by Charrolles (1988), Van Dijk (1997), Beaugrande and Dressier (1981), Koch and Travaglia (1993, 1995), Koch (2002, 2004) and Val (2000, 2004). We have established as aims to analyze and interpret meaning relations problems in how to articulate direct cited discourse with citing discourse and at the same time explain semantic implications that comes from that articulation that compromise text meaning, at background section in that monographic genre. The analysis, by qualitative and quantitative basis in eleven monographic works that form our corpus, gave us the opportunity to achieve and see that meaning relationships in the articulation of direct cited discourse with citing discourse show problems that may be categorized into three different groups: problems related to meaning relationships with citing discourse that comes before it, problems of meaning relationships with citing discourse that comes after it, and problems with of meaning relationships with citing discourse that come before it and at the same time with citing discourse that comes after it (i.e. in relation to both). These analysis also allow us assert that, these problems, just because they occur frequently, they affect the micro level text coherence, and they also compromise the text global meaning. The results show that students at Letras Course, even in the ending process of their course do not show the real domain in relation to some ways of direct cited discourse organization and working, and also how the ideas articulation work in the construction of relations between direct cited discourse and the citing discourse that can turn those students able to produce a text that enhance acceptable patterns